Balance Performance in Autism: A Brief Overview - Stins, John F.; Emck, Claudia (Frontiers in Psychology, 2018)
Children with autism not only have limited social an communicative skills; motor abnormalities are also clearly present, such as poor timing and coordination of balance. Moreover, impaired gross motor skills hamper participation with peers. Balance control is interesting from a cognitive science perspective, since it involves a complex interplay between information processing, motor planning, and timing and sequencing of muscle movements. In this paper we discuss the background of motor problems in children with autism, focusing on how posture is informed by sensory information processing. We also discuss the neurobiological basis of balance problems, and how this is related to anxiety in this group. We then discuss possible avenues for treatment of ASD symptoms, especially as regards movement-related interventions. Finally we present a theoretical outlook and discuss whether some of the symptoms in ASD can be understood from an embodied cognition perspective.